Legal Medicine in Europe The Past and the Future - Busuttil, Anthony (The Bulletin of Legal Medicine, 1996)
The "art of medicine as practised by the physician” have permeated and infiltrated the courts and the practice of law throughout known historical times. This influence has been well established on the Continent of Europe for over two thousand years though medical involvement in the law was well enshrined in forensic practice in Chinese, Persian, Arabic and other non-European civilisations well before the Greco-Roman era: for example, papyri relating to the times of Roman Occupation of Egypt refer to the advice and opinions sought from doctors by judges in reaching the more appropriate judicial verdicts.
Keywords: legal medicine; forensic medicine